Field trip as a tool to motivate students to learn Geoscience subject - Hasan, M.L. (American Scientific Publishers, 2017)
Some of the Petroleum Engineering students viewed Geoscience subject as not important in their study. However, this subject becomes significant when they have to apply Geoscience knowledge in other subjects such as drilling and well logging. Due to this, it is quite hard to maintain the interest and motivate the students to love Geoscience subject. A field trip was chosen as a tool to motivate and enhance students’ understanding regarding this subject. This paper evaluates the impact of field trip to motivate Petroleum Engineering students to learn Geoscience. The quantitative analyses were done based on surveys. Four elements to maintain and boost students’ motivation to learn: content, method/process, instructor/lecturer, environment were studied. Results show positive responses from the students after the field trip. © 2017 American Scientific Publishers. All rights reserved.